2017
DOI: 10.1186/s12874-017-0347-z
|View full text |Cite
|
Sign up to set email alerts
|

Grey literature in systematic reviews: a cross-sectional study of the contribution of non-English reports, unpublished studies and dissertations to the results of meta-analyses in child-relevant reviews

Abstract: BackgroundSystematic reviews (SRs) are an important source of information about healthcare interventions. A key component of a well-conducted SR is a comprehensive literature search. There is limited evidence on the contribution of non-English reports, unpublished studies, and dissertations and their impact on results of meta-analyses.MethodsOur sample included SRs from three Cochrane Review Groups: Acute Respiratory Infections (ARI), Infectious Diseases (ID), Developmental Psychosocial and Learning Problems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(187 citation statements)
references
References 24 publications
(31 reference statements)
5
176
1
5
Order By: Relevance
“…Last, we did not include grey literature in our search. However, it is doubtful that inclusion of such literature would alter our main findings, and one recent study shows that inclusion of such literature has limited impact on reviews (Hartling et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Last, we did not include grey literature in our search. However, it is doubtful that inclusion of such literature would alter our main findings, and one recent study shows that inclusion of such literature has limited impact on reviews (Hartling et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Second, largely driven by their brevity, abstracts may not contain adequate information for systematic reviewers to appraise the design, methods, risk of bias, outcomes, and results of studies reported in the abstracts [18][19][20][21]. Third, the dependability of results presented in abstracts also is questionable [22][23][24], which occurs at least in part because (1) most abstracts are not peer-reviewed and (2) results reported in abstracts are often preliminary and/or based on limited analyses conducted in a rush to meet conference deadlines. The most frequent types of conflicting information between abstract and full-length journal article have pertained to authors or authorship order, sample size, and estimates of treatment effects (their magnitude or, less frequently, direction) [25][26][27][28][29][30][31].…”
Section: Arguments Against Including Conference Abstracts In Systematmentioning
confidence: 99%
“…Searches were conducted from the inception of each database to May 2017 (Table S1). In line with guidance relating to searching, additional methods were adopted to improve the comprehensiveness of the searches (Brettle and Grant, 2004;Stansfield et al, 2016;Hopewell et al, 2007;Hartling et al, 2017…”
Section: Search Strategymentioning
confidence: 99%